Differential Responses of Bovine Monocyte-Derived Macrophages to Infection by Neospora caninum Isolates of High and Low Virulence - García-Sánchez, Marta; Jiménez-Pelayo, Laura; Horcajo, Pilar; Regidor-Cerrillo, Javier; Ólafsson, Einar B.; Bhandage, Amol K.; Barragan, Antonio; Werling, Dirk; Ortega-Mora, Luis Miguel; Collantes-Fernández, Esther (Frontiers in Immunology, 2019)
Neospora caninum, a protozoan parasite closely related to Toxoplasma gondii, represents one of the main causes of abortion in cattle. Macrophages (MØs) are mediators of the innate immune response against infection and likely one of the first cells encountered by the parasite during the host infection process. In this study, we investigated in vitro how high or low virulent isolates of N. caninum (Nc-Spain7 and Nc-Spain1H, respectively) interact with bovine monocyte-derived MØs and the influence of the isolate virulence on the subsequent cellular response. Both isolates actively invaded, survived and replicated in the MØs. However, Nc-Spain7 showed a higher invasion rate and a replication significantly faster, following an exponential growth model, whereas Nc-Spain1H presented a delayed replication and a lower growth rate without an exponential pattern. N. caninum infection induced a hypermigratory phenotype in bovine MØs that was characterized by enhanced motility and transmigration in vitro and was accompanied by morphological changes and abrogated extracellular matrix degradation. A significantly higher hypermotility was observed with the highly virulent isolate Nc-Spain7. Nc-Spain1H-infected MØs showed elevated reactive oxygen species (ROS) production and IL12p40 expression, which also resulted in increased IFN-γ release by lymphocytes, compared to cells infected with Nc-Spain7. Furthermore, IL-10 was upregulated in MØs infected with both isolates. Infected MØs exhibited lower expression of MHC Class II, CD86 and CD1b molecules than uninfected MØs, with non-significant differences between isolates. This work characterizes for the first time N. caninum replication in bovine monocyte-derived MØs and details isolate-dependent differences in host cell responses to the parasite.